Improving Students' Learning Ability in Islamic Religious Education Learning through the Contextual Teaching and Learning Method at SMA Negeri 1 Baktiya Barat - Mardalina (Jurnal Pendidikan Profesi Guru, 2025)
Islamic Religious Education is one of the subjects given from elementary to high school. PAI examines a set of events, facts, concepts and generations related to faith and belief in Allah swt. Through PAI subjects, students are directed to be able to become peace-loving world citizens. In the future, students will face tough challenges due to the life of a global society or are constantly changing at all times. Seeing the above reality and the problems faced in the implementation of teaching and learning activities, teachers must be able to find the right learning model by actively and creatively involving students. The author tries to apply one of the learning methods, namely the Contextual Teaching And Learning method, to reveal whether the Contextual Teaching And Learning method can improve students' learning abilities. In the Contextual Teaching And Learning method, students are more active in solving to find problems, while teachers play the role of mentors or provide instructions on how to solve problems. The purpose of this research is to improve the learning ability of students to learn Islamic Religion zakat material through the Contextual Teaching And Learning method for grade XI of SMA Negeri 1 Baktiya Barat North Aceh Regency. From the results of the study, it can be seen that the Contextual Teaching And Learning method in the zakat material of class XI shows an increase in the average class of 66, the initial condition of 66, the first cycle 76, and in the second cycle 86.